Mathematics for nurses - Erfelo, Rodolfo; Sirug, Winston S.;Turgueza, Amelita G. (Mandaluyong City, Philippines : Books Atbp. Publishing Corp, 2005)
This text provides the fundamental mathematics necessary to prepare students in nursing.
Chapter 1: Whole number arithmetic -- Chapter 2: Fractions -- Chapter 3: Decimal numerals -- Chapter 4: Principles of percentage -- Chapter 5: Ratio and proportion -- Chapter 6: System of measurement -- Chapter 7: Conversion between system of measurement -- Chapter 8: Interpreting drug orders -- Chapter 9: Oral dosage calculations.
Includes bibliographical references.
Keywords: NURSING -- MATHEMATICS